The Role of Marketing Strategies in Increasing Fertilizer Sales at PT. XYZ - Al Ubaidiyah, Arfaul Auni; Sukaris, Sukaris (Universitas Muhammadiyah Gresik, 2023)
This Marketing strategy plays an important role in a company, where fertilizer companies like PT. ABC are one of the companies that must have a marketing strategy, the more attractive the marketing strategy is being carried out will be able to capture a wider target market and will gain a larger number of customers. The research is aimed at identifying marketing strategies in the face of highly competitive business competition and to identify the role of management strategy in an effort to increase sales at the fertilizer company PT. ABC, where the company is a private fertilizer that is engaged in the field of processing mineral dolomite magnesium into dolomit fertilizers. In this study the author uses qualitative methods, data collection techniques using direct observation, interviews and documentation. From the results of the observations and also the interview the author can conclude that the role of the marketing strategy carried out by the PT. ABC has succeeded in increasing the sales of fertilizers by determining segmentation, targeting, positioning and performing marketing mix strategy (marketing mix) with four elements namely: Product, Price, Place, Promotion where the roles of marketing strategies carried on at the P.T. ABC have been running optimally and can be seen with the corner data that has experienced improvement in the last few months.